2003
DOI: 10.1007/bf03027257
|View full text |Cite
|
Sign up to set email alerts
|

Springback characteristics of tailor-welded strips in U-draw bending

Abstract: The purpose of this study is to investigate the springback characteristics of tailor-welded strips in U-draw bending. Two different welded strips were adopted to compare the effects of weld-line locations on the springback. One was welded along the centerline of the strip-width and the other was welded along the centerline of the strip-length. To investigate the effect of different thickness combinations on the springback, the tailorwelded strips were joined by a laser welding process. Three sheet thickness co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…It was suggested that for accurate prediction of springback, inclusion of weld zone should be addressed in further studies. Seo et al 17 investigated the effects of punch and die profile radii and blank holding force on springback behaviour of TWBs in a U-draw bending operation. It was observed that springback in both transverse and longitudinally welded strips reduced with an increase in blank holding force.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that for accurate prediction of springback, inclusion of weld zone should be addressed in further studies. Seo et al 17 investigated the effects of punch and die profile radii and blank holding force on springback behaviour of TWBs in a U-draw bending operation. It was observed that springback in both transverse and longitudinally welded strips reduced with an increase in blank holding force.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of springback behaviour of a TWB is more complex than a conventional blank due to the differences in properties or thickness and the presence of the weld. A few studies [13][14][15] have been carried out to characterize the springback phenomenon in TWBs. Chang et al 13 studied the effect of punch profile radius on springback in TWBs with weld line oriented in transverse and longitudinal directions in U-bending.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that springback in longitudinally welded TWB specimens was similar to that of the springback in thicker parent blank. Consequently, Seo et al 15 investigated the effects of blank holding force on the springback behaviour in TWBs in a U-bending operation. Albut and Brabie 16 studied the effect of rolling direction (RD) in U-draw bending of TWBs having the bend axis parallel to weld line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in springback due to thickness were also observed. It was noticed that the springback on thicker side decreased because of the combine springback effect on thinner side and weld line [18]. Differences in material properties provide different springback due to similar blank holding force, and thus, the control force would be needed for a symmetric part [19].…”
Section: Introductionmentioning
confidence: 99%